Escavações arqueológicas na missão de São Lourenço Mártir, São Luiz Gonzaga, RS, Brasil - Ribeiro, Pedro Augusto Mentz; Ribeiro, Catharina Torrano; Klamt, Sergio Celio; Buchaim, Joaquim Jorge Silveira (Estudos Ibero-Americanos, 1989)
-